Ice Action on Pairs of Cylindrical and Conical Structures - Kato,Kazuyuki; Sodhi,Devinder S (1983)
Ice action on two cylindrical and conical structures, located side by side, was investigated in a small-scale experimental study to determine the interference on the ice forces generated during ice-structure interaction. The proximity of the two structures changes the mode of ice failure, the magnitude and direction of ice forces on the individual structure, and the dominant frequency of ice force variations. Interference effects were determined by comparing the experimental results of tests at different structure spacings.